Pengaruh Kemandirian Belajar Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP Negeri 17 Kota Serang - Nurdiati, Tiara; Setiani, Yani; Firdos Santosa, Cecep Anwar Hadi (Peneliti.net, 2024)
This research aims to find out if there is an influence between learning independence and the mathematical problem solving ability of eight grade students at SMPN 17 Kota Serang. The type of research used is ex-post facto. A sample of sixty eighth grade students was taken using simple random sampling techniques. Data collection was carried out by giving tests and questionnaires. The results of the research show that there is a significant influence between learning independence on mathematical problem solving abilities and 17,1% of learning independence influences students’ mathematical problem solving abilities, the rest is outside the learning independence factor.